2016
DOI: 10.1038/mp.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

mGluR2/3 mechanisms in primate dorsolateral prefrontal cortex: evidence for both presynaptic and postsynaptic actions

Abstract: Cognitive deficits in psychiatric and age-related disorders generally involve dysfunction of the dorsolateral prefrontal cortex (dlPFC), but there are few treatments for these debilitating symptoms. Group II metabotropic glutamate receptors (mGluR2/3), which couple to Gi/Go, have been a focus of therapeutics based on rodent research, where mGluR2/3 have been shown to reduce axonal glutamate release and increase glial glutamate uptake. However, this strategy has had mixed results in patients, and understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 68 publications
5
36
0
Order By: Relevance
“…For example, both noradrenergic α 2A-AR and glutamatergic mGluR3 are concentrated on spines, where they enhance delay cell firing by inhibiting cAMP–K + channel signaling. 134,145 In contrast, mGluR2 are localized presynaptically, where they inhibit glutamate release. 146 Another critical regulator of feedforward cAMP–calcium signaling in newly evolved dlPFC layer III microcircuits is the phosphodiesterase, PDE4A, which catabolizes cAMP and is anchored to the spine apparatus by the scaffolding protein Disrupted in Schizophrenia (DISC1).…”
Section: Dynamic Network Connectivity Of Dlpfc Layer Iii: Unique Neurmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both noradrenergic α 2A-AR and glutamatergic mGluR3 are concentrated on spines, where they enhance delay cell firing by inhibiting cAMP–K + channel signaling. 134,145 In contrast, mGluR2 are localized presynaptically, where they inhibit glutamate release. 146 Another critical regulator of feedforward cAMP–calcium signaling in newly evolved dlPFC layer III microcircuits is the phosphodiesterase, PDE4A, which catabolizes cAMP and is anchored to the spine apparatus by the scaffolding protein Disrupted in Schizophrenia (DISC1).…”
Section: Dynamic Network Connectivity Of Dlpfc Layer Iii: Unique Neurmentioning
confidence: 99%
“…212 Physiological recordings from monkeys show that NAAG stimulation of mGluR3 in dlPFC greatly enhances delay cell firing by inhibiting cAMP–K+ channels signaling. 145 NAAG activity is inhibited by the NAAG peptidase GCPII. 213 A NAAG peptidase inhibitor markedly increased the firing of delay cells, 146 suggesting these agents may have therapeutic potential.…”
Section: Relevance Of Dnc Mechanisms In Dlpfc Layer III To Novel Thermentioning
confidence: 99%
See 1 more Smart Citation
“…Group II mGlu receptors are widely expressed in brain regions relevant to drug-related behaviors. Although physiological actions of postsynaptic group II mGlu receptors have been identified (for example see Otani et al, 2002; Walker et al, 2015; Jin et al, 2016), they are best known for their ability to inhibit presynaptic neurotransmitter release at glutamatergic terminals. Group II mGlu receptor activation depresses glutamate release in critical regions such as the mPFC (Otani et al, 1999, 2002; Huang and Hsu, 2008; Walker et al, 2015), dorsal striatum (Lovinger and McCool, 1995; Kahn et al, 2001), NAc (Manzoni et al, 1997; Robbe et al, 2002a,b), central amygdala (Neugebauer et al, 2000), and BNST (Grueter and Winder, 2005).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Accordingly, it was suggested that the mGlu2 receptor was expressed both pre- and post-synaptically in the frontal cortex [80,81], an hypothesis that has been validated recently [82]. Using neuroanatomical approaches such as fluorescent in situ hybridization (FISH) [36] and immunohistochemistry [83], it was demonstrated that 5-HT 2A and mGlu2 co-localized in layer V mouse cortical pyramidal neurons.…”
Section: Family a Gpcr Heteromers And Their Role In Receptor Functionmentioning
confidence: 99%